Distribusi Residu Logam Berat Timbal (Pb) dalam Organ Ikan Bandeng (Chanos chanos) PADA Salinitas Air Berbeda - Petrus Rani Pong-Masak; Rachmansyah Rachmansyah (Jurnal Perikanan Universitas Gadjah Mada, 2006)
Determination of plumbum (Pb) residue distribution in the organs of milkfish, Chanos chanos reared in different water salinities was performed in a 2,000 l fiberglass container under laboratory condition. Water salinity levels as treatment were 10, 20, and 30 ppt. Milkfishes (100±14 g) obtained from local farmer were reared in 2,000 l fiberglass container at density of 40 individu/l. The fishes were exposured with Pb at 2 ppm. Sampling were conducted at 0 (initial), 7, 14 and 21 days after application of Pb. Pb was extracted from flesh, kidney, liver, intestine, and gill, and determined by atomic absorption spectrophotometer. Results showed that Pb residue in milkfish organs increase when water salinity decrease. The highest Pb residue concentration found in kidney followed by liver, intestine, flesh and gill.